IMPLEMENTATION OF DEMOCRATIC EDUCATION THROUGH LEARNING CIVIC EDUCATION TO ESTABLISH RESPONSIBLE CITIZEN - Abdul Azis Wahab, Siti Rahmi Anjani, Dasim Budimansyah (Jurnal Civicus, 2014)
This research is aimed by the occurrence of deterioration of the learning process that led to the Civics students are less concentrated in the learning process. The results of the study of democratic education through Civic Education learning to form responsible citizens in Junior High School 2 Soreang generate active student learning, creative and innovative to make the grade as a laboratory of democracy, the educational content of democracy is equal rights and duties in school. The emergence of active students in school attitudes make the students are always active in school activities and are taught to always be responsible for the act of doing as a form of education shape the success from the democratic process of responsible.